Role of European mitochondrial DNA haplogroups in the prevalence of hip osteoarthritis in Galicia, Northern Spain. Issue 01 (17th February 2009) - Rego, I; Fernández-Moreno, M; Fernández-López, C; Gómez-Reino, J J; González, A; Arenas, J; Blanco, F J
Abstract : Objective: To analyse the mitochondrial DNA (mtDNA) haplogroups of patients with hip osteoarthritis (OA) and those of healthy controls in a Spanish population. Methods: mtDNA haplogroups were assigned to 550 cases of hip OA and 505 clinically asymptomatic controls. Sets of controls with healthy knees and hips (n = 179) and patients with knee and/or hip OA (n = 977) were also analysed in a multivariate analysis after adjusting for sex, age and smoking. Results: Individuals carrying haplogroup J showed a significantly decreased risk of developing hip OA (OR 0.661; 95% CI 0.440 to 0.993; p = 0.045). In addition to haplogroup J, smoking protected against the development of hip OA (OR 0.543; 95% CI 0.311 to 0.946; p = 0.031). However, no relationship was found between rheumatoid arthritis and mtDNA haplogroups. Conclusion: The results of this study support the hypothesis that the mtDNA haplogroups have a role in the complex osteoarthritic process.